Molecular diagnosis of somatic overgrowth conditions: A single‐center experience. Issue 3 (13th February 2019) - Lalonde, Emilie; Ebrahimzadeh, Jessica; Rafferty, Keith; Richards‐Yutz, Jennifer; Grant, Richard; Toorens, Erik; Marie Rosado, Jennifer; Schindewolf, Erica; Ganguly, Tapan; Kalish, Jennifer M.; Deardorff, Matthew A.; Ganguly, Arupa
Abstract: Background: Somatic overgrowth conditions, including Proteus syndrome, Sturge–Weber syndrome, and PIK3CA ‐related overgrowth spectrum, are caused by post‐zygotic pathogenic variants, result in segmental mosaicism, and give rise to neural, cutaneous and/or lipomatous overgrowth. These variants occur in growth‐promoting pathways leading to cellular proliferation and expansion of tissues that arise from the affected cellular lineage. Methods: We report on 80 serial patients evaluated for somatic overgrowth conditions in a diagnostic laboratory setting, including three prenatal patients. In total, 166 tissues from these 80 patients were subjected to targeted sequencing of an 8‐gene panel capturing 10.2 kb of sequence containing known pathogenic variants associated with somatic overgrowth conditions. Deep next‐generation sequencing was performed with the IonTorrent PGM platform at an average depth typically >5, 000×. Results: Likely pathogenic or pathogenic variants were identified in 36 individuals and variants of unknown significance in four. The overall molecular diagnostic yield was 45% but was highly influenced by both submitted tissue type and phenotype. In the prenatal setting, two patients had pathogenic variants identified in cultured amniocytes but in a third patient, the pathogenic variant was only present in post‐natal tissues. Finally, expanding the test to include full gene sequencing of PIK3CA in contrast to targeted sequencing identified likely pathogenic variants in 3 of 7 patients that tested negative on the original panel. Conclusion: Next‐generation sequencing has enabled sensitive detection of somatic pathogenic variants associated with overgrowth conditions. However, as the pathogenic variant allele frequency varies by tissue type within an individual, submission of affected tissue(s) greatly increases the chances of a molecular diagnosis. Abstract : Clinical genetic testing with deep next‐generation sequencing of 166 specimens from 80 patients with suspected mosaic overgrowth conditions resulting a 45%–61% diagnostic yield and was highly influenced by the tissue submitted and phenotype. Three prenatal cases illustrate remaining challenges in prenatal diagnosis of mosaic overgrowth syndromes.